A Genetic Algorithm with a Trust Model Function for Detecting Sinkhole and Wormhole Nodes in Wireless Sensor Networks - Seidu, Rafiw; Salifu, Abdul-Mumin Selanwiah; Ansuura, Johnbosco A. K. (Transactions on Engineering and Computing Sciences, 2024)
This study delved into wireless sensor networks, comprising numerous nodes with limited energy, computation, and transmission capabilities. Wireless sensor networks face security challenges due to their vulnerability to capture and compromise in insecure environments. Malicious nodes exploit communication's wireless nature, engaging in sinkhole and wormhole attacks. To address this, we propose a genetic strategy utilising a trust-based formula as a fitness function to evaluate sensor node reliability. Nodes progressing beyond a trust threshold criterion are identified, isolating malicious nodes responsible for attacks. Implemented in MATLAB 2018a, our approach effectively identifies and isolates such nodes, as demonstrated by the results.